If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10s + -95 = 4s + -23 Reorder the terms: -95 + 10s = 4s + -23 Reorder the terms: -95 + 10s = -23 + 4s Solving -95 + 10s = -23 + 4s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-4s' to each side of the equation. -95 + 10s + -4s = -23 + 4s + -4s Combine like terms: 10s + -4s = 6s -95 + 6s = -23 + 4s + -4s Combine like terms: 4s + -4s = 0 -95 + 6s = -23 + 0 -95 + 6s = -23 Add '95' to each side of the equation. -95 + 95 + 6s = -23 + 95 Combine like terms: -95 + 95 = 0 0 + 6s = -23 + 95 6s = -23 + 95 Combine like terms: -23 + 95 = 72 6s = 72 Divide each side by '6'. s = 12 Simplifying s = 12
| 18=3(18)-36 | | y=3-5/2x | | 3z-36=z | | 80/2= | | 3b=10b-84 | | 2t+4+2t-3t=2+2 | | x^2-18x+26=-6 | | -2*0(0+2-5)+3(-5*0+2*2)+2(6*0+2-8)= | | 3a-69=a+13 | | 4v-51=v | | 10=4+2k | | 10v-51=v+57 | | 5(6x-1)+4(11-5x)-3(3x+3)=-6 | | 2q-79=q-28 | | 2s-4=s | | 8u-1=5u+14 | | 10c-20=c+34 | | s+3=2s | | 6+3g=18 | | 84=6(d+10) | | 5(m-73)=80 | | (5x+1.3y)+(2.9x-0.6y)= | | -19x+23x=44 | | 4*x+3=43 | | 1/3(2p-1) | | 7/42=49 | | 5(0)+y=2 | | 27-5p=14-4p | | 13-(3m+4)=5+2m-11 | | 4n-6=-2n+18 | | -3*(x+5)=-15 | | -3*x+5=-15 |